The fermentation of Roselle juice by five selected strains of yeast - Sevilla, Ursula L.; Guzman, Matilde P. (1970.)
This study has been motivated by the problem of producing higher alcohol levels in the fermentation of roselle juice, an acid drink from the calyxes of a wild plant of Central Luzon. Five strains of yeast, whose fermenting properties have been proven in previous investigations, were used to inoculate the juices. The "syruped" method of fermentation was employed wherein only a part of the total amount of sugar was added to the juice at the start of the fermentation. The rest of the sugar was added during the course of fermentation. Objective tests for alcohol, pH, and acidity as well as subjective and microbiological tests were performed to evaluate the resulting roselle wines. Results of three trials showed that the yeast strain S. sake produced the highest level of alcohol. The yeast strain S. ellipsoideus var. Montrachet gave wines that had the highest flavor scores.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Fermentation